Exercise resisted with weights in the reduction of the body fat practitioners of the musculação in the town of Cacoal / RO - Cuenca, Renam Natel (2012)
The present study it has for purpose to verify if the resisted exercise promotes alteration in the corporal composition. Today already it is possible to find research that defends this type of work for individuals with raised percentage of fat, alleging that a raised lean mass more generates an expense bigger caloric thus causing a reduction in the percentage of fat without it has also a reduction in the muscular mass generally causes for diets. This work comes to show that through the exercises also resisted it is possible to have a reduction in the percentage of fat and modifications in the total corporal mass. They had been part of this research 63, being of the masculine and feminine sex with ages between 18 and 35 years physically active. In this research it was evaluated, the percentage of fat through the mensuração of cutaneous folds and total corporal mass, in the daily pay and after-training, having been that these data had been retrospective of pupils who had only carried through exercises resisted in an academy. To the end of the work, that had duration of twelve weeks, a reduction of the percentage of fat was observed. It also had increase in the Total corporal mass, (corporal weight).